Microbial Landscape In Current Clinical Cardiac Surgery - SalamaninaА. О.; Borysenko, K. Yu.; VandaТ. М.; KanavetsТ. P. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Currently in clinics, the study of microbial landscape is an important component allowing antimicrobials to be pre-scribed even before obtaining data on a possible agent causing infectious complication and its sensitivity to antibiotics. Study of microbial landscape can be used in medical practice in order to forecast the risk of infectious complications in patients with heart pathology admitted for surgical intervention at a cardiac surgery institution for timely, adequate and specific selec-tion of an antibiotic, and thus to improve efficacy of treatment and reduce the patient’s stay in a hospital as much as possible. Microbial monitoring included 192 patients hospitalised during 2016 who were in the intensive care unit and received antibacterial agents for a long time, patients transferred from other hospitals, patients of ≤1 year of age, as well as patients in whom acute and chronic infectious foci and concomitant diseases are detected. During the study, 519 isolates were obtained from 354 samples. The analysis included 249 cultures of specified micro-organisms, isolated from clinical material most commonly. The analysis shows the increasing role of coagulase-negative staphylococci, especially Staphylococcus haemolyticus (77 (31%)) and Klebsiella pneumoniae (54 (21.7%)). Data providing information on a change in microbiota at a hospital and presence of hospital strains contribute to timely performance of sanitary and antiepidemic measures in order to prevent intrahospital infections.